1981
DOI: 10.3181/00379727-167-41211
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical and Biological Properties of Horse Parathyroid Hormone

Abstract: A . 163. S c r i~i c~i~ Bioph~siqirc~. CHU St Atitoitic. 27. riio Chciligtiy. 75.571 Paris CcJi1c.r 12. Frtitici): r i t i d "'INSERM U.90. H(5pittil Ncckc>r. 161, riic i1c Si.i-rc.s. 7.5730 Priris Crile~.r 15. FrtiticoAbstract. Intact, biologically active parathyroid hormone (1 -84) extracted from horse parathyroid glands was detected by heterologous amino terminal radioimmunoassays and heterologous carboxyl terminal radioimmunoassay using antibovine parathyroid hormone antibodies. The immunochemical behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This hypothesis seems reasonable, since it is known that the part of the PTH molecule that shows less interspecies variation is the aminoterminal end (Potts et al 1995). In addition, equine PTH has been reported to be very similar to human PTH in the aminoterminal portion (Raulais et al 1981); therefore, heterologous antibodies should be more likely to bind the most aminoterminal part of the PTH molecule. In any case, it is well known that the activity of the PTH molecule is due to the aminoterminal sequence of the molecule (Treagear et al 1973).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis seems reasonable, since it is known that the part of the PTH molecule that shows less interspecies variation is the aminoterminal end (Potts et al 1995). In addition, equine PTH has been reported to be very similar to human PTH in the aminoterminal portion (Raulais et al 1981); therefore, heterologous antibodies should be more likely to bind the most aminoterminal part of the PTH molecule. In any case, it is well known that the activity of the PTH molecule is due to the aminoterminal sequence of the molecule (Treagear et al 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic effects of PTH on bone are produced by the amino-terminal portion of the hormone (1-34, 1-37, 1-38). It is reported that the human PTH fragment does not show any structural differences from the equine one 19 . The dose of hPTH (1-37) chosen for this investigation was 0.5 mg kg 21 BW, which is comparable to the dosage in humans.…”
Section: Discussionmentioning
confidence: 97%
“…125 I-human PTH and 125 I-human CT were used for assays. Cross reactivity of the carboxyterminal of human and the equine PTH was investigated and validated [18,19]. Cross reactivity between human and equine CT was also proved by radioimmunoassay [9] and immunohistochemistry [3].…”
mentioning
confidence: 99%